Analisis Hukum Ekonomi Syariah tentang Prinsip Collateral dalam Penyaluran Pembiayaan Akad Murabahah pada Bank Mega Syariah Kantor Cabang Bandung - Hanifah Dhamier Nurahman; Zaini Abdul Malik; Iwan Permana (UNISBA Press, 2022)
Abstract. In the economy in Indonesia, especially in banking, of course, we generally know the principles of 5C financing analysis, namely, character (character), capacity (capacity), capital (capital), collateral (collateral), and condition of economic (economic condition). Financing risk can affect the level of profitability of Islamic Financial Institutions. Therefore, the financing and investment disbursed must be maintained and managed prudently so as not to become problematic financing (Non-Performing Financing). Collaterals should get attention that collateral does not cause bad financing to become good financing, at least the financing will get better. The formulation of the research problem is: 1. What are the provisions of the Collateral principle in Islamic Economic Law? 2. What are the provisions of the Collateral principle in Bank Mega Syariah? 3. How is the Sharia Economic Law Analysis on Collateral Principles in the Distribution of Murabahah Contract Financing at Bank Mega Syariah Bandung Branch Office? The research method used in the preparation of this research is through a normative-empirical approach using field research data collection techniques and library research.This study concludes that murabahah financing is characteristically a pure investment product and Islamic banks require customers to submit collateral with an agreement as a form of the customer's ability to return funds. Collateral is a form of confidence and prudence of Islamic banks in distributing financing and measuring the ability of customers to carry out their obligations to manage the business and bring benefits that are needed together. Abstrak. Dalam perekonomian di Indonesia, khususnya dalam perbankan tentu kita secara umum telah mengenal prinsip analisis pembiayaan 5C yaitu, character (karakter), capacity (kapasitas), capital (modal), collateral (jaminan), dan condition of economic (kondisi perekonomian). Risiko pembiayaan dapat mempengaruhi tingkat profitabilitas Lembaga Keuangan Syariah. Maka dari itu pembiayaan dan investasi yang disalurkan harus dijaga serta dikelola dengan hati-hati (prudential) agar tidak menjadi pembiayaan yang bermasalah (Non-Performing Financing). Collateral kiranya perlu mendapatkan perhatian bahwa collateral tidak menyebabkan pembiayaan yang jelek menjadi pembiayaan yang baik, paling tidak pembiayaan tersebut menjadi lebih baik. Rumusan masalah penelitian ini adalah: 1. Bagaimana ketentuan prinsip Collateral dalam Hukum Ekonomi Syariah? 2. Bagaimana ketentuan prinsip Collateral yang ada di Bank Mega Syariah? 3. Bagaimana Analisis Hukum Ekonomi Syariah tentang Prinsip Collateral dalam Penyaluran Pembiayaan Akad Murabahah pada Bank Mega Syariah Kantor Cabang Bandung? Metode penelitian yang digunakan dalam penyusunan penelitian ini adalah melalui pendekatan normatif-empiris dengan menggunakan teknik pengambilan data riset lapangan dan riset kepustakaan. Penelitian ini menyimpulkan pembiayaan murabahah secara karakteristiknya merupakan produk investasi murni dan pihak bank syariah mewajibkan nasabah untuk menyerahkan jaminan dengan perjanjian sebagai bentuk kemampuan nasabah mengembalikan dana. Jaminan menjadi salah satu bentuk keyakinan dan kehati-hatian bank syariah dalam menyalurkan pembiayaan dan mengukur kemampuan nasabah melakukan kewajibannya untuk mengelola usaha dan mendatangkan keuntungan yang dibutuhkan bersama.